Strategic plan for Intercrafts Perú - Hein, Walter (Pontificia Universidad Católica del Perú, 2019)
Intercrafts Peru Inc. has been working side by side with Peruvian handcrafts producers for over ten years and it is currently going through a financial and organizational downturn. The company has experienced net losses for the past three years and there is a need to implement changes that can revert this situation by putting the company back on track to achieve sustainable long term grow. The organization is subjected to trade practices established by the World Fair Trade Organization (WFTO) and it is through this practices that the company has established long term relationships with customers in North America, Europe and Oceania. However changes in the industry and internal inefficiencies limit the capacity of Intercrafts to increase the number of sales reaching new customers. The company was born as an initiative of the (Interregional Central of Peruvian Artisans) CIAP and explains the low bargaining power towards the suppliers because of the relationship. Furthermore this bond reinforces the social commitment of the organization from its conception, to support the sustainable development of the artisans and their environment. It is in this commitment that the company can exploit most of the potential strengths and opportunities. In this context this strategic plan proposes the use of three strategies to take the company from its current situation to the desired situation to be the best crafts exporting company in Peru in 2020: (a) Product development through strategic alliances, creating new designs capacitating the artisans to improve the products; (b) Retrenchment, restructuring some of the company’s processes to reduce costs and have an efficient operational system; and (c) Market penetration attacking the high end niche market with improved marketing.

Intercrafts Perú Inc. ha trabajado de la mano con productores de artesanía peruanos por más de 10 años y actualmente se encuentra en una mala situación financiera y organizacional. La compañía ha operado los tres últimos años incurriendo en pérdidas. Existe una necesidad por realizar cambios que puedan revertir esta tendencia y poner a la compañía en un camino de crecimiento sostenido en el largo plazo. La organización está sujeta a las prácticas de comercio establecidas por la Organización Mundial de Comercio Justo y es a través de estas prácticas que ha conseguido relaciones de largo plazo con clientes en Norte América, Europa y Oceanía. Sin embargo cambios en la industria e ineficiencias internas limitan la capacidad de Intercrafts para ampliar la base de clientes actual. La compañía nace como una iniciativa de la Central Interregional de Artesanos del Perú (CIAP). Y en esta relación se explica el bajo poder de negociación que existe hacia los proveedores. Sin embargo esta relación también refuerza el compromiso social de la compañía que, desde su concepción, está dedicada a apoyar al desarrollo sostenible de los artesanos y su entorno. Es aquí en donde se encuentras potenciales oportunidades y fortalezas que Intercrafts necesita explotar. Es en este contexto que este plan estratégico plantea el uso de estrategias para llevar a la compañía del estado actual a ser la exportadora número uno de artesanías peruanas en el 2020: (a) Desarrollo de producto alianzas estratégicas, fortaleciendo la relación con CIAP con capacitaciones y creación de diseños innovadores; (b) Atrincheramiento, reestructurando algunos de los procesos de la compañía con el fin de disminuir costos y ser más eficientes; y (c) Penetración de mercado, atacando nichos en el sector más elevado del mercado con una nueva técnica de mercadeo.
Keywords: Artesanía--Perú; Organizaciones sin fines de lucro; Planificación estratégica; https://purl.org/pe-repo/ocde/ford#5.02.04